PENGEMBANGAN WEB SISTEM INFORMASI KARYA ILMIAH DENGAN MENGGUNAKAN PHP DAN MYSQL - Ansar, Asri; Soleh, Mohammad; Widyastuti, Naniek (Jurnal Script, 2013)
ABSTRACTScientific Work is a form of accountability by the lecturer and the real embodiment of Tri Dharma college. The Tri Dharma University includes, education and teaching, research and development as well as society dedication (Abdimas).Â The benefits of this scientific work is expected to provide accurate results and efficient as a goal for the development of the data results of scientific work that was obtained from the lecturer. With the Web Scientific Information System, the faculty can make it easier to access the data of scientific work. At the site built using the programming language PHP and uses a MySQL database processing. This site is expected to make it easier for users to input data and view the data results of scientific work of other professors. From some of the results of this scientific work of data can generate reports in the field of scientific research works in detail. Information of this scientific work can also be a library that can be used for scientific work on the other lecturers. Â Keywords: Society Dedication (Abdimas), Teaching, Research.